(3cJGH GdeCNhPGJs - (3GQTejOSs
(3ChdgG (B:s
(3Cf eKGdI efShHI Edi CQTejOS HgG CTcGd MSfI bdjdI GdYOO cKjQI GdahGFO ai CUhd GdgfOSI s
(3BNQgG (B:s
(3JeJ GdeCNhPGJ dCTejOS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHY YTQs
(3GdfSNI HgG MhGTs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1455s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs